Plasma Acute Phase Proteins as Predictors of Chronic Lung Allograft Dysfunction in Lung Transplant Recipients - Janciauskiene S; Royer PJ; Fuge J; Wrenger S; Chorostowska-Wynimko J; Falk C; Welte T; Reynaud-Gaubert M; Roux A; Tissot A; Magnan A (Dove Medical Press, 2020)
Sabina Janciauskiene,1,2,* Pierre-Joseph Royer,3,* Jan Fuge,1 Sabine Wrenger,1 Joanna Chorostowska-Wynimko,2 Christine Falk,4,5 Tobias Welte,1 Martine Reynaud-Gaubert,6 Antoine Roux,7– 9 Adrien Tissot,3 Antoine Magnan3 1Department of Pulmonary and Infectious Diseases, BREATH German Center for Lung Research (DZL) Hannover University School, Hannover, Germany; 2Department of Genetics and Clinical Immunology, National Institute of Tuberculosis and Lung Diseases, Warsaw, Poland; 3CHU de Nantes, Centre National De Référence Mucoviscidose Nantes-Roscoff, Nantes, France; 4Institute of Transplant Immunology, Hannover Medical School, Hannover, Germany; 5German Center for Infection Research DZIF Hannover Braunschweig Site, TTU-IICH, Hannover, Germany; 6Department ofPulmonary Diseases and Lung Transplantation, CHU Nord de Marseille; IHU - Méditerranée Infection, Aix Marseille Université, Marseille, France; 7Hôpital Foch, Suresnes, France; 8Université Versailles Saint-Quentin- en-Yvelines, Versailles, France; 9 l’Institut du Thorax, Université de Nantes, Nantes, France*These authors contributed equally to this workCorrespondence: Sabina Janciauskiene Department of Pulmonary and InfectiousDiseases, Hannover Medical School, Feodor-Lynen Str. 23, Hannover 30625, GermanyTel +49-511-532-7297Email Janciauskiene.sabina@mh-hannover.deAbstract: Cumulating reports suggest that acute phase proteins (APPs) have diagnostic and prognostic value in different clinical conditions. Among others, APPs are proposed to serve as markers that help to control the outcome of transplant recipients. Here, we questioned whether plasma concentrations of APPs mirror the development of chronic lung allograft dysfunction (CLAD). We performed blinded analysis of serial plasma samples retrospectively collected from 35 lung transplanted patients, of whom 25 developed CLAD and 10 remained stable during the follow-up period of 3 to 4.5 years. Albumin (ALB), alpha1-antitrypsin (AAT), high sensitivity C-reactive protein (CRPH), antithrombin-3 (AT3), ceruloplasmin (CER), and alpha2-macroglobulin (A2MG) were measured by the nephelometric method. We found that within the first six months post-transplantation, levels of A2MG, CER and AAT were higher in stable patients relative to those who later developed CLAD. Moreover, in stable patient’s plasma CRPH levels decreased during the follow-up period whereas opposite, in those developing CLAD, the CRPH gradually increased. The ALB levels became significantly lower at the end of the follow-up period in CLAD relative to a stable group. A logistic regression model based on A2MG, CER and AT3 at cut-offs levels of ≥ 175.5 mg/dL, ≥ 37.8 mg/dL and ≥ 27.35 mg/dL enabled to discriminate between stable and CLAD patients with a sensitivity of 87.5%, 100% and 62.5%, and specificity of 65.9%, 72.7% and 79.5%, respectively. We identified A2MG (below  175.5 mg/dL) as an independent predictor of CLAD (hazard ratio 11.5, 95% CI (1.5– 91.3), p< 0.021). Our findings suggest that profiles of certain APPs may help to predict the development of lung dysfunction at the very early stages after transplantation.Keywords: acute phase proteins, transplantation, allograft dysfunction